An ab-initio computational investigation into the properties of potentially ultra-hard metal oxynitrides - Mmethi, Fiki Martin (My University, 2009)
Ab-initio calculation are undertaken to compare some phases of several metal oxynitrides namely: titanium (TiON), tantalum (TaON), niobium (NbON), and tungsten (WON). The crystal structures considered follow that found in zirconia (ZrO2) namely monoclinic, cubic, tetragonal, and orthorhombic. Bulk moduli and relative energies are obtained for each of the structures. In general it is found that quite high hydrostatic pressures are needed for synthesis of these materials although each of them exhibit quite significant compressibility. Diamonds is a super hard material useful for many applications but it’s expensive to manufacture and its applications is somehow limited. The analyses here were carried out to examine properties of the oxynitride phases and estimate the pressure needed for a synthesis of such phases. These alloys are expected to have variety of interesting and novel future industrial application in many fields.